DAVIES, Jr., THOMAS M., Indian Integration in Peru: A Half Century of Experience, 1900-1948, University of Nebraska Press, Lincoln, Nebraska, 1974;204págs. - Klaiber, Jeffrey (1978)
No contiene resumen